Memoria y postmemoria en Rigoberta: la nieta de los mayas (Revista de Crítica Literaria Latinoamericana, 2025)
In her autobiography, Crossing Borders, Rigoberta Menchu revisits the painful memory of her Mayan ancestors as well as articulates her own personal trauma as seen in her testimony I' Rigoberta Menchu: An Indian Woman in Guatemala. Through postmemory the Guatemalan activist is able to connect with the transgenerational legacy of her community as well as narrate her own past through the imaginative recovery of memory. In this way, she confirms that memory and postmemory as a creative endeavor are vital components of the reconstruction of the past.
Keywords: Autobiography; Memory; Postmemory; Rigoberta Menchú; Testimony; Trauma